A conceptual paper on perception of society and social entrepreneurship intention among business graduates in Bangladesh moderated by innovation - Haque, A. K. M. Ahasanul; Hashim, Junaidah; Mustaffa, Nur Fariza; Sarker, Md. Atiqur Rahman; Anis, Zohurul (2019)
Social entrepreneurship is contributing towards the welfare of society since it creates social value characterized by innovation. This concept is growing worldwide in order to solve existing social problem through entrepreneurship. Though, entrepreneurship in Bangladesh is raising rapidly among business graduates, social entrepreneurship is still a new concept here. This study aims to investigate the relationship between the perception of society and the intention of business graduates for social entrepreneurship in Bangladesh. This study will be primarily in conceptual nature and it will provide overview of existing literature on social entrepreneurship. Extensive literature review will be done based on which there will be a reflective analysis. This conceptual paper will contain definitions, concepts and characteristics of social entrepreneurship. However, this study will be extended in future with primary data collection and quantitative analysis. Based on the social network theories of innovation, this study will reveal the relationship between perception of society and social entrepreneurship intention of business graduates. The findings of the study will draw the attention of policy makers to emphasis on social entrepreneurship development among business graduates who have the high chances of success due to academic background and enthusiasm. Moreover, practitioner will be benefitted from the conceptual framework of this study in order to promote social entrepreneurship.